Comparing the effectiveness and safety of Dinoprostone vaginal insert and double-balloon catheter as cervical ripening treatments in Chinese patients - Yan, Jinjing; Yin, Baomin; Lv, Hanghang (Frontiers in Medicine, 2022)
Background This retrospective study was to compare the effectiveness and safety of Dinoprostone vaginal insert vs. double-balloon catheter as cervical ripening agents for labor induction. Methods Pregnant women with Bishop score <7, who received either Dinoprostone vaginal insert 10 mg or Cook's double-balloon catheter for labor induction, were studied. The primary outcome was the rate of vaginal delivery within 48 h; the secondary outcomes were the proportion of women undergoing cesarean section, labor duration, oxytocin administration, changes in Bishop score, complications during labor, and maternal/neonatal outcomes. Results One hundred and eighty-two women were included in Dinoprostone group, and 199 women were in double-balloon catheter group. The rate of vaginal delivery within 48 h was significantly higher in Dinoprostone group than that in double-balloon catheter group (90.11% vs. 75.38%, P = 0.0002). There were 18 cesarean section deliveries (9.89%) in Dinoprostone group and 49 cesarean section deliveries (24.62%) in double-balloon catheter group, with significant differences between two groups (P = 0.0002). The duration of labor was higher in Dinoprostone group, while the augmentation with oxytocin was significantly lower in Dinoprostone group than in double-balloon catheter group (all P < 0.0001). The incidence of chorioamnionitis was significantly higher in double-balloon catheter group as compared with Dinoprostone group (0 vs. 12, P = 0.0005), while neonatal outcomes were similar in two groups. Conclusion Dinoprostone vaginal insert as cervical ripening agent is more effective for labor induction and with lower risks of chorioamnionitis as compared with double balloon catheter in Chinese populations.